Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1038/s42003-021-02903-7
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative allostery and structural dynamics of streptavidin at cryogenic- and ambient-temperature

Abstract: Multimeric protein assemblies are abundant in nature. Streptavidin is an attractive protein that provides a paradigm system to investigate the intra- and intermolecular interactions of multimeric protein complexes. Also, it offers a versatile tool for biotechnological applications. Here, we present two apo-streptavidin structures, the first one is an ambient temperature Serial Femtosecond X-ray crystal (Apo-SFX) structure at 1.7 Å resolution and the second one is a cryogenic crystal structure (Apo-Cryo) at 1.1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…These differences between room-temperature and cryogenic crystallography structures have been experimentally observed for several proteins. [86][87][88][89][90][91][92][93] A careful analysis of our NQO1 structure has further revealed that residues Tyr128 and Phe232, which play a key role in the function of the protein, [94][95][96][97][98] show an unexpected flexibility within the crystals (Fig. 7(a)).…”
Section: Droplet Generation and Injection Performancementioning
confidence: 99%
“…These differences between room-temperature and cryogenic crystallography structures have been experimentally observed for several proteins. [86][87][88][89][90][91][92][93] A careful analysis of our NQO1 structure has further revealed that residues Tyr128 and Phe232, which play a key role in the function of the protein, [94][95][96][97][98] show an unexpected flexibility within the crystals (Fig. 7(a)).…”
Section: Droplet Generation and Injection Performancementioning
confidence: 99%
“…DeChancie estimated an enthalpic binding energy of −6.75 kcal/mol that would need to be compensated for by the ligand in order to capitalize on the potential entropic gain . Very recently, a fully solvated, ambient temperature apo structure of streptavidin with seven waters in the biotin binding pocket (Figure E) using serial femtosecond X-ray crystallography was solved to a resolution of 1.7 Å . All five calculated ice-like ring waters would be displaced by biotin’s two five-membered rings (Figure D), while the three waters observed crystallographically would be displayed by the ureido ring alone (Figure F).…”
Section: Water Solvation Of the Ligand And Protein Unbound Statesmentioning
confidence: 99%
“…(E) Seven biotin binding pocket waters observed in the ambient temperature apo structure of streptavidin (PDB 7EK8). (F) Seven biotin binding pocket waters overlaid with biotin. PDB 3RYU was used for the biotin bound depictions.…”
Section: Introductionmentioning
confidence: 99%
“…The SFX measurements were conducted at the Macromolecular Femtosecond Crystallography (MFX) end station of the Linac Coherent Light Source (LCLS) at the SLAC National Accelerator Laboratory. A bCcO microcrystal slurry was loaded into a gas tight syringe and driven by a HPLC pump into a 100 µm diameter capillary of a Microfluidic Electrokinetic Sample Holder (MESH) injector, 39,40 which has recently been developed as a useful and reliable technique for delivering microcrystal slurries into the XFEL beam [55][56][57][58][59] . A high voltage (~+2500 V) was applied to the sample at the entrance of the capillary against a grounded waste collector.…”
Section: Methodsmentioning
confidence: 99%